ظاهرة النصب في قراءة سعيد بن جبيرت سنة 559 دراسة لغوية - عبدالله, محمد خالد محمد (Sulaimani Journal for Humanities, 2003)
Abstract In preparing this brief subject for discussing those words that are (Mansub) in (Said's Ibn Jubiar) 's reading for sacred koran. I have realized some information which deal with his reading and the way of his reading. Although those words that are in his reading are few. The information are: 1) Some of those differences are between the reading of Koran in the way Koran has been written and the reading of (Ibn Jubair), the causes are: a) In the few differences that are in using words between the Arab tribes especially in those words that are nouns such as: the tribe of (Said Ibn Jubair) in using the meaning of (Al-Salam, Al-musalm, Al-musslih) he uses the word (Silm), and other Arab tribes use the word (Salam). b) Some words in sacred Koran have many forms and many analysis. In the beginning writing this words in the Koran has its reading in some forms, because Koran has been collected in the period of (Osman Ibn Afan) and some copies have been written and sent for the cities of Basrah, Kufa, Sham and Mecca, one copy of this writing has put in Medina, its words have no marks on or under them and it has been written as the Arab writing has been written. In the time of (Abdul Malid Ibn Marwan) the words have been marked and punctuated, he ordered the ruler of Iraq (Hajaj) in (Wasit) city and (Hassan Yahya Ibn Yamur) help him to classify Koran into some parts except the (Hizib) part. He wrote the words in Koran without putting any mards on or under the words which need the marks. He suited these words with their meanings in Koran, he allowed the reader to read the word as it is possible for him to read. His special reading deals with the form or the analysis or the singular or the plural of the word or the way of using the word which gives the real meaning or the way of using the word in other place instead of its place which does not give the real meaning. In (Ibn Jubair) 's reading the words which deal with this subject are: (Yastatia, Rabuka, Khalissat, Khalissan, Ebadan, Atihar, Tasma, Alssum, Makara, Tarkabna). 2. Ibn Jubair's way in reading those words that come in the form of (Mansub) is that he wanted to choose that meaning which the (Mansub) word gives in the beginning (the real meaning) and he neglected the meaning which the word gives in other place instead of its place. This point is very clear in the word (Makara) in the (Saba) 34 and 33. 3. Most of those words he has read in the form of (Mansub) are the words that give their meanings completely and directly and these words are away of those that don't give their purposes, this point is clear in his reading generally and in the word (Akun) in (Munafiqwn) 163 in the line 10, he read this word like that (Akwun). 4. He uses those rules that are right and away of criticism and most of the Arab linguists use those rules. Those rules deal with the language that the scientists of syntax (Al-najat) has put the linguistics' rules. Because of this in his reading, the scientists say that his readings are very (clear, correct and suitable) and his readings almost come in correct speech.